Pharmacokinetic Modification of Controlled Release Tablets of Antihypertensive Drug - Palanisamy Vishnu (Journal of Global Pharma Technology, 2019)
The objective of the study was to pharmacokinetic modification of controlled release tablets  of Isradipine tablets designed to provide 24 hours drug release profile using varying proportion of Eudragit L – 100 and HPMC Phthalate; Lactose monohydrate as matrix-forming material. The prepared matrix tablets showed satisfactory physicochemical properties where drug content was 99.19 % to 103.78 %, thickness was 3.23 mm to 3.36 mm, hardness was 3.37±0.13 to 3.51±0.20 kg/cm2 , friability was less than 1% and % weight variation was within the standard pharmacopoeial limits of ±10% of the weight. Mathematical analysis of the release kinetics of the optimized formulation (F15) was best fitted in zero order kinetics (R2 = 0.982). The dissolution profiles of formulation FI4 and innovator product in multi media were compared in Phosphate buffer pH 6.8.Several kinetic models respectively. The stability data reveals that the FI4 showed a negligible change in drug content thickness, weight variation, hardness, friability and in vitro drug release for three months according to ICH guidelines.